Grist mill road eaudiobook A novel. - Yates, Christopher J. (Macmillan Audio, 2018)
"Four distinct voices tell the story of a disturbing incident and its far-reaching aftermath...It's a labyrinth of shifting perspectives, but the narrators keep this grim story focused and mesmerizing." — AudioFile Magazine The highly anticipated new audiobook from the author whose debut was called "The smart summer thriller you've been waiting for...The novel you should be reading tonight" (NPR's All Things Considered ) and was named a Book of the Year by NPR and an Entertainment Weekly Must-List Pick Christopher J. Yates's cult hit Black Chalk introduced that rare writerly talent: a literary author who could create a plot with the intricacy of a brilliant mental puzzle, and with characters so absorbing that listeners are immediately gripped. Yates's new audiobook does not disappoint. Grist Mill Road is a dark, twisted, and expertly plotted Rashomon-style tale. The year is 1982; the setting, an Edenic hamlet some ninety miles north of New York City. There, among the craggy rock cliffs and glacial ponds of timeworn mountains, three friends—Patrick, Matthew, and Hannah—are bound together by a terrible and seemingly senseless crime. Twenty-six years later, in New York City, living lives their younger selves never could have predicted, the three meet again—with even more devastating results. More praise for Grist Mill Road: "[Dan] Bittner, Will Damron, Graham Halstead, and Saskia Maarleveld bring the multidimensional characters vividly to life and narrate this complex and twisting tale of psychological suspense in a manner that keeps the listener involved and eager to follow along to its harrowing conclusion." — Booklist